Starch Biosynthesis in Guard Cells But Not in Mesophyll Cells Is Involved in CO2-Induced Stomatal Closing. Issue 2 (21st April 2016) - Azoulay-Shemer, Tamar; Bagheri, Andisheh; Wang, Cun; Palomares, Axxell; Stephan, Aaron B.; Kunz, Hans-Henning; Schroeder, Julian I.
Abstract : Stomatal CO2 response and assimilation rates of defined starch biosynthesis mutants (ADGase and pPGI) reveal that starch synthesis in guard cells but not mesophyll functions in CO2 -induced stomatal closure. Abstract: Starch metabolism is involved in stomatal movement regulation. However, it remains unknown whether starch-deficient mutants affect CO2 -induced stomatal closing and whether starch biosynthesis in guard cells and/or mesophyll cells is rate limiting for high CO2 -induced stomatal closing. Stomatal responses to [CO2 ] shifts and CO2 assimilation rates were compared in Arabidopsis ( Arabidopsis thaliana ) mutants that were either starch deficient in all plant tissues (ADP-Glc-pyrophosphorylase [ADGase]) or retain starch accumulation in guard cells but are starch deficient in mesophyll cells (plastidial phosphoglucose isomerase [pPGI]). ADGase mutants exhibited impaired CO2 -induced stomatal closure, but pPGI mutants did not, showing that starch biosynthesis in guard cells but not mesophyll functions in CO2 -induced stomatal closing. Nevertheless, starch-deficient ADGase mutant alleles exhibited partial CO2 responses, pointing toward a starch biosynthesis-independent component of the response that is likely mediated by anion channels. Furthermore, whole-leaf CO2 assimilation rates of both ADGase and pPGI mutants were lower upon shifts to high [CO2 ], but only ADGase mutants caused impairments in CO2 -induced stomatal closing. These genetic analyses determine the roles of starch biosynthesis for high CO2 -induced stomatal closing.